2019
DOI: 10.1007/s10113-019-01474-y
|View full text |Cite
|
Sign up to set email alerts
|

Climate information to support wildlife management in the North Central United States

Abstract: This paper investigates what is needed to make climate and weather information more usable for the wildlife management practitioners and ecological researchers in the Prairie Potholes Region (PPR) of the North Central United States. Using interviews, policy document analysis, and participant observation, we identify climate and weather information needs, barriers to use, and opportunities to provide better information to these users. We found that the research and management communities need guidance on how to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…2020) using climate‐modeling best practices (Sofaer et al. 2017) for managing this ecosystem of continental and global importance (Yocum and Ray 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020) using climate‐modeling best practices (Sofaer et al. 2017) for managing this ecosystem of continental and global importance (Yocum and Ray 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multiple wetland monitoring efforts have been sustained for over three decades and enabled the development of different modeling tools and approaches to assess how climate change could impact wetlands and waterbirds in the PPR (Johnson and Poiani 2016, McIntyre et al 2019, McKenna et al 2019. Despite past efforts to forecast the future impact that climate change may have on prairie-pothole wetlands, the conservation and management community has identified the need for more robust and relevant climate/wetland projections (Rushing et al 2020) using climate-modeling best practices (Sofaer et al 2017) for managing this ecosystem of continental and global importance (Yocum and Ray 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these models use variables that influence the climate variability of the region and capture seasonal climate information and trend. Capturing this variability is important because managers are very interested in the climate variability of the region [8]. These models exhibit high skill exemplified by high linear correlation values and low RMSE in LOOCV mode.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Near-term threats include land modification due to agriculture or oil/gas well production and climate variability, and longer-term threats include climate change. Managers must respond to both, though near-term threats typically take priority for addressing within agency resource constraints [8]. Complicating matters further, much of the land in the United States portion of the PPR is privately owned [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that social context, professional cultures and organizational structures have an effect on information use by professionals [42][43][44][45], while the user's discipline, type of activity, personality, and experience with data, influence how they search for information [46]. In addition, aspects of the data, such as how and for what purposes data were produced within a discipline, appear to be important in generating trust to facilitate data use by researchers [47].…”
Section: Introductionmentioning
confidence: 99%